China's Arctic Ambitions and What They Mean for Canada - Lajeunesse, Adam (Beyond Boundaries: Canadian Defence and Strategic Studies, 2018)
China's Arctic Ambitions and What They Mean for Canada is one of the first in-depth studies of China's increasing interest in the Arctic. It offers a holistic approach to understanding Chinese motivations and the potential impacts of greater Chinese presence in the circumpolar region, exploring resource development, shipping, scientific research, governance, and security. Drawing on extensive research in Chinese government documentation, business and media reports, and current academic literature, this timely volume eschews the traditional assumption that Chinese actions are unified and monolithic in their approach to Arctic affairs. Instead, it offers a careful analysis of the different, and often competing, interests and priorities of Chinese government and industry. Analyzing Chinese interests and activities from a Canadian perspective, the book provides an unparalleled point of reference to discuss the implications for the Canadian and broader circumpolar North.